K2S2O8‐Mediated Oxysulfonylation of Vinyl Azides with Sodium Sulfinates to Access β‐Keto Sulfones in Water. Issue 10 (8th March 2021) - Luo, Mengqiang; Ren, Xiaorong; Shen, Runpu; Qi, Chenze; Zhang, Yaohong; Wang, Hai
Abstract: With water as solvent, K2 S2 O8 mediated facile and efficient synthesis of β‐keto sulfones through oxysulfonylation of vinyl azides with sodium sulfinates is described. The novel procedure has the advantages of being environmentally benign, mild reaction conditions, short reaction time, easy and simple operation, wide tolerance of functional groups, which establish the practical application of this methodology. Abstract : K2 S2 O8 catalyzed oxysulfonylation of vinyl azides with sodium sulfinates to access β‐keto sulfones in water is described and the possible mechanism for the reaction has been proposed based on the results of the control experiments, which indicated that the reaction involved a radical pathway. The novel procedure has the advantages of being eco‐friendly, mild reaction conditions, short reaction time, easy and simple operation, wide tolerance of functional groups, which establish the practical application of this methodology.